Mechanical design and force control algorithm for a robot leg with hydraulic series-elastic actuators. (8th May 2020) - Shi, Yapeng; Wang, Pengfei; Zha, Fusheng; Sun, Lining; Li, Mantian; Jia, Wangqiang; Li, Zhibin
This article presents a mechanical design structure for hydraulic actuators using the principle of series-elastic actuator, considering the restriction of mechanical structure, weight and size, as well as the requirement of high joint torques due to the large payload. An articulated leg was designed to incorporate with two of these elastic elements symmetrically for each joint. Further, for the hydraulic system with a position servo loop, a force control algorithm was particularly proposed and developed for joint torque tracking and Cartesian impedance control. Finally, a number of experiments were carried out on the leg platform, and the experimental results validated the effectiveness of the force control algorithm and the performance of the overall system.